Re-coding homes through flexible interiors emerging research and opportunities - Onay, Nilufer Saglar 1976-; Garip, S. Banu 1977-; Garip, Ervin 1977- (IGI Global, 2019)
"This book examines the importance of combined structured research and design studies in the field of interior architecture. It discusses issues like flexibility, adaptability, and user-centered approaches in interior design studies by focusing on a research project called "A User-Centered Model Research Towards a Flexible Interior Spatial Design for Mass Housing Units"--
Description based on title screen (IGI Global, viewed 07/04/2019)
Keywords: Interior architecture; Interior decoration; Modular coordination (Architecture); Apartment houses; Housing